1997
DOI: 10.1093/ndt/12.5.1007
|View full text |Cite
|
Sign up to set email alerts
|

Continuous administration of intravenous iron during haemodialysis

Abstract: A simple, safe and potentially cost effective method of giving intravenous iron to patients receiving regular haemodialysis therapy is described. The heparin and iron are mixed in normal saline and given as a continuous infusion via the syringe pump present on the modern dialysis machine. No pharmacological incompatibility was observed between iron polymaltose and Heparin Choay or Heparin Roche. No adverse reactions attributable to i.v. iron were observed in over 400 patients and more than 30,000 dialyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
3
8
0
1
Order By: Relevance
“…A substantial finding was the significantly lower incidence of ADRs associated with FCM compared with iron polymaltose, inferring greater patient tolerance of FCM infusions. The incidence of ADRs for iron polymaltose and FCM found in this study were within the ranges of widely varying documented rates across published studies, from less than 3.6% to 31% for iron polymaltose and 1% to 25% for FCM, and with only rare (≤1%) incidences of anaphylaxis …”
Section: Discussionsupporting
confidence: 80%
“…A substantial finding was the significantly lower incidence of ADRs associated with FCM compared with iron polymaltose, inferring greater patient tolerance of FCM infusions. The incidence of ADRs for iron polymaltose and FCM found in this study were within the ranges of widely varying documented rates across published studies, from less than 3.6% to 31% for iron polymaltose and 1% to 25% for FCM, and with only rare (≤1%) incidences of anaphylaxis …”
Section: Discussionsupporting
confidence: 80%
“…It is true that 1.7% of the patients receiving iron dextran have anaphylactoid reactions [69], but an international survey found that these reactions are reported far less commonly with iron gluconate than with iron dextran [70]. Similarly, in contrast to iron dextran, the use of iron sucrose in over 15,000 injections in over 300 patients has, in our experience [62], not been associated with any serious reactions, results similar to those reported by others with the use of iron gluconate [71]. In addition, iron sucrose appears to release iron more readily, to yield higher transferrin saturation levels, and to increase ferritin levels more rapidly than iron dextran [72].…”
Section: Quo Vadis?supporting
confidence: 82%
“…Similarly, during this time, we have also administered 200 mg IV iron saccharate given in 150 ml normal saline over 1 hour to 47 continuous ambulatory peritoneal dialysis patients once every few weeks without a single adverse reaction. A similar low record of adverse effects during HD has been seen with IV iron polymaltose ( 55). Note that serious reactions, such as hypersensitivity and anaphylaxis, have been found to occur in approximately 0.7% of patients ( 56) receiving IV iron dextran.…”
Section: Safety Of IV Iron In Pd Patientssupporting
confidence: 58%